1980
DOI: 10.1111/j.1476-5381.1980.tb07036.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐induced Bronchial Anaphylaxis in Actively Sensitized Guinea‐pigs: Anti‐anaphylactic Effects of Sodium Cromoglycate and Aminophylline

Abstract: The inhibitory effects of sodium cromoglycate (SCG) and aminophylline on antigen‐induced bronchial anaphylaxis in guinea‐pigs, actively sensitized according to different regimens, were examined. SCG (1 mg/kg administered intravenously) reduced the anaphylactic response in animals sensitized with 1 μg ovalbumin (OA) together with Al(OH)3 100 mg, and challenged at 14 and 40 days after sensitization. If higher doses of antigen (10 μg OA together with Al (OH)3 or 5 mg OA on day 0 plus 10 mg OA on day 2) were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

1981
1981
1996
1996

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…IgE and allergic hyperreactivity The method used for generation of antiserum in this study has been reported to evoke IgE formation in this species (12). To ascertain whether IgE-mediated responses contributed to acute allergic bronchospasm or allergic hyperreactivity, serum was heated for 4 hr at 56'C, prior to intravenous injection.…”
Section: Airway Obstruction and Airway Hyperreactivitymentioning
confidence: 99%
“…IgE and allergic hyperreactivity The method used for generation of antiserum in this study has been reported to evoke IgE formation in this species (12). To ascertain whether IgE-mediated responses contributed to acute allergic bronchospasm or allergic hyperreactivity, serum was heated for 4 hr at 56'C, prior to intravenous injection.…”
Section: Airway Obstruction and Airway Hyperreactivitymentioning
confidence: 99%
“…Thus higher provocation doses are needed to obtain an effect and much more histamine is released after anaphylactic challenge in guinea-pigs sensitized to produce a mixture of IgG and IgE antibodies compared with those sensitized to produce only IgG antibodies (Andersson, 1980a; 0007-1188/82/100301-07 $01.00 Andersson & Bergstrand, 1981). Furthermore, disodium cromoglycate (SCG) and glucocorticoids do not prevent IgG-mediated bronchial anaphylaxis (Andersson, 1980b; Andersson & Bergstrand, 1981; Andersson & Brattsand, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier investigation it was observed that a bronchial anaphylactic reaction which, at least partly, is mediated by IgE-like antibodies, is greatly inhibited by acute treatment with SCG, whereas an IgG-mediated reaction is not. Theophylline inhibits both IgG-and IgE-mediated reactions (Andersson, 1980b). However, long-term treatment with the investigated compounds would possibly be more relevant to the clinical situation.…”
Section: Introductionmentioning
confidence: 99%